Tree Species Effects on Soils: Implications for Global Change Proceedings of the NATO Advanced Research Workshop on Trees and Soil Interactions, Implications to Global Climate Change August 2004 Krasnoyarsk, Russia - Binkley, Dan.; Menyailo, Oleg.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Almost 50% of the total area of Austria is forested, and the forests are dominated by commercially valuable stands of Norway spruce ( (Picea abies). The few remaining forests that resemble the natural vegetation composition are located in forest reserves with restricted management. These natural forests are used as reference systems for evaluating silvicultural research on sustainable forest management. Natural forests are expected to have high biodiversity, where the structural richness of the habitat enables complex relationships between fauna, flora, and microflora. They also provide refugia for rare plants and animals found only in natural forest types. Austria had 180 of these forest reserves up to the year 2003. Most of these forests are privately owned, and owners are compensated by the government for loss of income associated with conservation status. The Ministerial Conference for the Protection of Forest Ecosystems (MCPFE) has launched a world-wide network of protected forest areas which should cover all major forest types (MCPFE and UNECE/FAO, 2003). The sites selected for our investigation of soil conditions and communities were chosen by vegetation ecologists and soil scientists. The stands have developed under natural competition conditions with no management interventions. All sites were well documented with known forest history. Our set of sites spans gradients of environmental conditions as well as species composition, providing a realistic evaluation of the interactions of biotic and abiotic factors.
Gaining Insights on the Effects of Tree Species on Soils -- Effects of British Columbia Tree Species on Forest Floor Chemistry -- Nutrient Turnover, Greenhouse Gas Exchange and Biodiversity in Natural Forests of Central Europe -- Tree Species Effects on Nitrogen Cycling and Retention: A Synthesis of Studies Using 15N Tracers -- Tree Species Management and Nitrate Contamination of Groundwater: A Central European Perspective -- Plant Effects on Soils in Drylands: Implications for Community Dynamics and Ecosystem Restoration -- The Response of Belowground Carbon Allocation in Forests to Global Change -- How Nitrogen-Fixing Trees Change Soil Carbon -- Effects of Tree Species on C- and N-Cycling and Biosphere-Atmosphere Exchange of Trace Gases in Forests -- Significance of Forests as Sources for N2O and NO -- Microbial Processing of Humic Substances from Meadow and Forest Soils -- Phosphorus Compounds Under Different Plants in an Artificial Soil Formation Experiment -- Short-Term Kinetics of Soil Microbial Respiration $1 (BA General Parameter Across Scales? -- The Influence of Stand Density on Growth of Three Conifer Species -- The Siberian Afforestaton Experiment: History, Methodology, and Problems -- Productivity of Six Tree Species Plantations for Three Decades in the Siberian Afforestation Experiment -- Biochemistry of Carbon and Nitrogen in the Siberian Afforestation Experiment -- Tree Species Effects on Potential Production and Consumption of Carbon Dioxide, Methane, and Nitrous Oxide: The Siberian Afforestation Experiment -- The Formation of Soil Invertebrate Communities in the Siberian Afforestation Experiment -- The Transformation of Plant Residues Under Different Tree Species in the Siberian Afforestation Experiment -- Tree Diversity and Soil Biology: A New Research Program in French Guyana.s
Keywords: Life sciences; Ecosystems; Forestry; Soil science; Soil conservation; Life Sciences; Ecosystems; Forestry; Soil Science & Conservation; Electronic books